Strong violet and green-yellow electroluminescence from silicon nitride thin films multiply implanted with Si ions - Ding, Liang (2010)
Strong visible electroluminescence (EL) has been observed from a 30 nm silicon nitride thin film multiply implanted with Si ions and annealed at 1100  degree celcius. The EL intensity shows a linear relationship with the current transport in the thin film at lower voltages, but a departure from the linear relationship with a quenching in the EL intensity is observed at higher voltages. The EL spectra show two primary EL bands including the predominant violet band at ∼ 3.0 eV (415 nm) and the strong green-yellow band at ∼ 2.2 eV (560 nm). Two weak bands including the ultraviolet band at ∼ 3.8 eV and the near infrared band at ∼ 1.45 eV emerge at high voltages. The evolution of each EL band with the voltage has been examined. The phenomena observed are explained, and the EL mechanisms are discussed.